Mergers and acquisitions and greenfield foreign direct investment in selected ASEAN countries - Moghadam, Alireza Tavakol; Mazlan, Nur Syazwani; Chin, Lee; Ibrahim, Saifuzzaman (Center for International Economics/Sejong University, 2019)
Multinational enterprises undertake Foreign Direct Investments mainly through two different modes: Mergers and Acquisitions and greenfield investments. In the sizable empirical literature that examines the determinants of Foreign Direct Investments, very few studies investigated the determinants of these modes. This article empirically analyzes the extent to which determinants such as market size, exchange rate, and market openness in six selected ASEAN countries (ASEAN-6) influence the choice of one entry mode of Foreign Direct Investments over the other. A robust relationship between market size and exchange rate with greenfield inflows rather than Mergers and Acquisitions sales is found. Additionally, given an increase in market openness, foreign firms prefer Mergers and Acquisitions to greenfield investments. The results also confirm the fire-sale Foreign Direct Investments phenomenon during financial crises.